A Review of the Blowfish Algorithm Modifications in Terms of Execution Time and Security - Abdul Qader, Raghad Abdul Hadi; AL-Wattar, Auday H. Saeed (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Data has become increasingly popular for advanced digital content transmission. Researchers are concerned about the protection of data. The transmission of digital data over a network has made multimedia data vulnerable to various threats, including unauthorized access and network hacking. As a result, the data must be protected with encryption methods based on symmetric encryption algorithms, which will ensure the data security. The Blowfish encryption algorithm is one of the most well-known cryptographic algorithms. However, each of the current algorithms has its own set of advantages and disadvantages. However, there are several drawbacks to using this algorithm, including complex computational operations, fixed (S-Box) and pattern issues, which can arise while dealing with more complex data, including texts. Many academics have sought to increase the algorithm's efficiency. The modifications to the Blowfish algorithms provided by researchers in prior works are summarized in this publication.